2015
DOI: 10.1016/j.toxicon.2015.07.009
|View full text |Cite
|
Sign up to set email alerts
|

eNOS uncoupling in the cerebellum after BBB disruption by exposure to Phoneutria nigriventer spider venom

Abstract: Numerous studies have shown that the venom of Phoneutria nigriventer (PNV) armed-spider causes excitotoxic signals and blood-brain barrier breakdown (BBBb) in rats. Nitric oxide (NO) is a signaling molecule which has a role in endothelium homeostasis and vascular health. The present study investigated the relevance of endothelial NO synthase (eNOS) uncoupling to clinical neurotoxic evolution induced by PNV. eNOS immunoblotting of cerebellum lysates processed through low-temperature SDS-PAGE revealed significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…PNV also activates neurons, and induces expression of GFAP, S100 and pro-inflammatory cytokines in astrocytes of the cerebellum and hippocampus with evidences of nitric oxide (NO) derived from neuronal and endothelial nitric oxide synthase (nNOS, eNOS, respectively) mediation [33,34,35]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PNV also activates neurons, and induces expression of GFAP, S100 and pro-inflammatory cytokines in astrocytes of the cerebellum and hippocampus with evidences of nitric oxide (NO) derived from neuronal and endothelial nitric oxide synthase (nNOS, eNOS, respectively) mediation [33,34,35]. …”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the rise in the expression of Cav-1 (WB and IHC data) promoted by PNV suggests eNOS inhibition and poor availability of oxide nitric (NO) and thus endothelium dysfunction. Recent study of our group has shown that PNV proper reduces availability of NO by leading to eNOS uncoupling [35]; at early periods following envenomation when toxic manifestation is severe, there is monomerization of eNOS and incapacity of the enzyme to produce NO, leading to superoxide production and endothelial/vascular BBB dysfunction [54]. …”
Section: Discussionmentioning
confidence: 99%
“…Some cases of phoneutrism can evolve to death. 1,3,6,7 Spiders of the genus Latrodectus (Walcknaer, 1805) (Aranae: Theridiidae) have a worldwide distribution occurring on many continents and islands. The genus Latrodectus contains about 31 species of spiders identified, which are commonly known as black widows.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, it was suggested that eNOS-derived NO is a neuromodulator that participates in the BBB-mediated control of the cerebellum in experimental models [36].…”
Section: •−mentioning
confidence: 99%
“…Therefore, the NO produced by NOS results in vasodilation and controls vascular resistance, platelet adhesion and aggregation, leukocyte-to-endothelium interaction, and the maintenance of BBB integrity [36].…”
Section: •−mentioning
confidence: 99%